2022
DOI: 10.3390/antiox11040668
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative, Antidiabetic, and Hypolipidemic Properties of Probiotic-Enriched Fermented Camel Milk Combined with Salvia officinalis Leaves Hydroalcoholic Extract in Streptozotocin-Induced Diabetes in Rats

Abstract: Antioxidative, antidiabetic, and hypolipidemic properties of probiotic-enriched fermented camel milk (FCM) combined with Salvia officinalis L. leaves hydroalcoholic extract (SOHE) in streptozotocin-induced diabetes in rats were investigated. Phytochemicals analysis and antioxidant capacity indicated that S. officinalis contained high phenolics with super antioxidant activity. Subsequently, HPLC analysis demonstrated 13 phenolic acids and 14 flavonoids in considerable amounts with ferulic acid and resveratrol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Similar results regarding the oxidative stress markers were recorded in previous studies showed that diabetic rats had much higher renal MDA levels than control animals, along with significantly lower levels of antioxidant enzymes, GSH, and SOD. (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results regarding the oxidative stress markers were recorded in previous studies showed that diabetic rats had much higher renal MDA levels than control animals, along with significantly lower levels of antioxidant enzymes, GSH, and SOD. (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with multiple studies [ 11 , 42 ]; the long fermentation time (72 h) resulted in the most significant increase in total phenolic compounds. Biologically, phenolic compounds are considered as health-promoting agents [ 43 , 44 , 45 , 46 ]. Cereal fermentation can modify the presence of these compounds due to enzymatic activities derived from both the grains and the microbes [ 23 ]; enzymes such as glycosidase, hydrolase, esterase, and β-glucosidase produced by different types of bacterial strains can improve the availability of the grains’ phenolic compounds [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significant differences in liver and kidney diagnostic markers were observed in the treated groups compared to the positive control group. The significant increase in ALT, AST, ALP, and T. Bili enzyme activities in the positive control group due to the STZ injection represents normal deterioration associated with diabetic liver injury [ 44 , 46 ]. The intervention of all subjected extracts resulted in significant improvements in balancing the liver enzyme levels in a dose- and type-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant potential, regulation of blood pressure, interaction with gut microbiota, suppression of pro-inflammatory cytokine overproduction, and activation of antioxidant enzymes are only some of the mechanisms by which functional foods have been demonstrated to aid in disease control [ 32 , 48 , 49 ]. Biologically active substances like phenolic compounds have been lauded for their ability to combat metabolic diseases and as effective antioxidant substances, neutralizing free radicals including hydrogen peroxide, hydroxyl radicals, and superoxide anion [ 50 ].…”
Section: Discussionmentioning
confidence: 99%